My man Godfrey - La Cava, Gregory, 1892-1952; Powell, William, 1892-1984; Lombard, Carole, 1908-1942; Hatch, Eric, 1901-1973.; Universal Pictures Company; Cinetel Films ([North Hollywood, CA] : Universal Productions, Inc., 1936)
During a riotous society scavenger hunt for a "forgotten man," Lombard finds Powell living in a rubbish dump. She hires him as a butler; and he changes each member of her rich, mad family, while finding new purpose in his own life. A classic screwball comedy of the 1930's.
Based on the novel by Eric Hatch.
William Powell, Carole Lombard, Gail Patrick, Alice Brady, Eugene Pallette, Jean Dixon.
Cinematographer, Ted Tetzloff; editors, Ted Russell, Kent Schoengarth; music, Charles Previn.
In English or Spanish.
Winner of National Film Registry, in 1999
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 9, 2015).
Keywords: Families -- Drama; Butlers -- Drama; Man-woman relationships -- Drama; New York (N.Y.) -- Drama; Romance films; Screwball comedy films; Comedy films; Internet videos; Streaming video